Pelatihan Penyusunan Bahan Ajar Bahasa Indonesia Beoreintasi Kearifan Lokal Madura bagi Guru SDI Al Munawwarah Pamekasan untuk Peningkatan Layanan Pendidikan Peserta Didik - Harsono; Rahmad; Royyan Julian; Abdul Hadi; Achmad Mufid (Universitas Lancang Kuning, 2022)
This service activity refers to the problems of SDI Al Munawwarah Pamekasan teachers in compiling teaching materials that are not in accordance with the systematic development of teaching materials. The second problem is that the text that is used as a discourse does not yet accommodate local wisdom. This activity was carried out in the form of workshop activities in the SDI Al Munawwarah meeting room. In this service, workshop activities have been carried out in the form of providing material and assistance in the preparation of local wisdom-oriented Indonesian language which begins with the concept of teaching materials and their development, text-based learning, and the exploration of Madurese local wisdom. This activity has provided an understanding to the workshop participants in compiling teaching materials that are in accordance with the guidelines by combining Madurese local wisdom and learner learning modalities. The results of the study of the prepared teaching materials describe the improvement in ability in terms of the mechanism for the preparation of teaching materials so that they can be used as teaching materials in classroom learning. The teaching materials that have been produced need to be tested for their effectiveness on an ongoing basis.